Primary anti-phospholipid antibody syndrome causing recurrent venous thrombosis and thrombocytopenia in a patient with Addison's disease. (5th December 2014) - Elebrashy, Ibrahim; Yousief, Elham; Saif, Aasem
Lesson: We report a case of Addison's disease presenting with recurrent deep venous thrombosis and thrombocytopenia and proved to have primary anti-phospholipid antibody syndrome. The case report highlights the shared autoimmune nature of both diseases.